Ag–Cu mixed phase plasmonic nanostructures fabricated by shadow nanosphere lithography and glancing angle co-deposition. (28th November 2016) - Ingram, Whitney; Larson, Steven; Carlson, Daniel; Zhao, Yiping
Abstract: By combining shadow nanosphere lithography with a glancing angle co-deposition technique, mixed-phase Ag–Cu triangular nanopatterns and films were fabricated. They were prepared at different compositions with respect to Ag from 100% to 0% by changing the relative deposition ratio of each metal. Characterizations by ellipsometry, energy dispersive x-ray spectroscopy, and x-ray diffraction revealed that the thin films and nanopatterns were composed of small, well-mixed Ag and Cu nano-grains with a diameter less than 20 nm, and their optical properties could be described by an effective medium theory. All compositions of the nanopattern had the same shape, but showed tunable localized surface plasmon resonance (LSPR) properties. In general, the LSPR of the nanopatterns redshifted with decreasing composition. Such a relation could be fitted by an empirical model based on the bulk theory of alloy plasmonics. By changing the colloidal template and the material deposited, this fabrication technique can be used to produce other alloy plasmonic nanostructures with predicted LSPR wavelengths.